2014
DOI: 10.1002/ijc.28699
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Nrf2 suppresses glioblastoma angiogenesis by inhibiting hypoxia-induced activation of HIF-1α

Abstract: Concerns were increasingly raised that several types of cancers overexpressed the nuclear factor erythroid 2-related factor 2 (Nrf2), which contributed strikingly to cancer biological capabilities and chemoresistance. However, the role of Nrf2 in the tumor vascular biology had yet to be mechanistically determined. Here, we investigated the involvement of Nrf2 in glioblastoma (GB) angiogenesis in hypoxia. First, we detected the overexpression of Nrf2 and correlated its protein level with microvessel density (MV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 44 publications
2
75
0
Order By: Relevance
“…The regulation of HIF-1α by Nrf2 has been investigated in tumor angiogenesis. Suppression of Nrf2 inhibited HIF-1α and resulted in a reduction of VEGF and blood vessel formation in human glioma cells (17) and colon cancer cells (13). Reduced mitochondrial O 2 consumption accounts for the degradation of HIF-1α in Nrf2-deficient cancer cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The regulation of HIF-1α by Nrf2 has been investigated in tumor angiogenesis. Suppression of Nrf2 inhibited HIF-1α and resulted in a reduction of VEGF and blood vessel formation in human glioma cells (17) and colon cancer cells (13). Reduced mitochondrial O 2 consumption accounts for the degradation of HIF-1α in Nrf2-deficient cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…We next investigated the role of Nrf2 on reparative angiogenesis in the ischemic retina. Nrf2 has been found to play an important role in angiogenesis in other contexts, both with respect to vascular development (12) and pathologic setting, such as tumor angiogenesis (13,17). To determine the importance of Nrf2 in ischemic retina, we compared wild-type (Nrf2…”
Section: Genetic Ablation Of Nrf2 Impedes Vascular Regeneration Andmentioning
confidence: 99%
“…Cells were cultured as monolayers in Ham's F12 medium supplemented with 10% FBS and antibiotics. Primary mouse alveolar epithelial cells were prepared from C57BL/6 mice as reported previously (26), with some modification (see the online supplement for details).…”
Section: Cell Culturementioning
confidence: 99%
“…However, the function of Nrf2 action may be much broader since it also regulates angiogenesis; for example, it may promote the formation of blood vessels to protect the retina from oxidative injury that occurs following hyperoxic stimulation (42). Furthermore, it has been demonstrated that downregulation of Nrf2 inhibits cancer cell vasculogenesis and migration in vivo and in vitro (21)(22)(23). These results indicate that the Nrf2/ARE signaling pathway may potentially contribute to the growth of DAVFs through the angiogenesis induced by VH.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 contributes to the protection of tissues from damage induced by the outside environment, including damage arising from inflammation, trauma, ischemia, hemorrhage and cancer (18,19). Other studies have identified an association between Nrf2 and angiogenesis (20) and it was demonstrated that the absence of Nrf2 may suppress cancer cell angiogenesis and migration in vivo and in vitro (21)(22)(23). However, the association between DAVF and Nrf2 in the pathogenesis of DAVF remains unclear.…”
Section: Introductionmentioning
confidence: 99%